Lithium ion battery negative electrode bionic binder and preparation method thereof, lithium ion battery negative electrode slurry and negative electrode
By introducing nucleic acid bases into the PAA-based lithium battery binder system, forming a lithium-ion battery negative electrode bionic binder with strong adhesion in the electrolyte, the binder swells or swells in the electrolyte in the prior art. The problem of dissolution has achieved improvements in the stability and circulation performance of the electrode structure.
Patent Information
- Application Number
- CN202411543121.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
AI Technical Summary
The existing lithium-ion battery binder swells or dissolves in the electrolyte, resulting in a decrease in adhesion and inability to effectively maintain the integrity of the electrode structure and cycling performance.
The nucleic acid base is introduced into the PAA-based lithium battery binder system, and the nucleic acid base acrylate and acrylic monomer are prepared by double bond modification to free radical copolymerization, forming a lithium-ion battery negative electrode biomimetic with strong adhesion in the electrolyte Adhesive.
Maintain the integrity and mechanical strength of the electrode structure under high surface load, significantly improve the cycle stability and electrochemical performance of lithium-ion batteries, and the preparation method is green and environmentally friendly, suitable for large-scale production.
Smart Images

Figure CN119242221A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery negative electrode bionic binder and a preparation method thereof, a lithium ion battery negative electrode slurry and a negative electrode. Background Art
[0002] With the transformation of the global energy structure, lithium-ion batteries, as an important carrier of clean energy, are facing unprecedented development opportunities, and market demand continues to grow. Binders, as one of the important auxiliary materials of lithium-ion batteries, mainly function to adhere active substances and conductive agents to the current collector to ensure that the electrode materials do not fall off, which has an important impact on the electrochemical performance of the battery.
[0003] Adhesion performance is a major evaluation index of lithium battery binders, which affects the cycle life of the battery. Currently, the binders widely used in commercial applications include polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), etc. PVDF is mainly used in positive electrodes, and its adhesion mainly comes from intermolecular forces, which are small; SBR and CMC are mainly used in negative electrodes, and their dispersibility is poor, and they are easy to swell, resulting in poor adhesion, and need to be used with CMC; PAA is currently mainly used in silicon-based negative electrodes, which has high adhesion, but the cohesive force between PAA molecules is large, which makes the pole piece easy to fall off at high surface loading, affecting the battery cycle performance.
[0004] Chinese patent application CN106040113A discloses a method for preparing a base biomimetic viscous polyacrylamide hydrogel system, and nucleic acid bases are introduced into the polyacrylamide hydrogel system, so that the polyacrylamide hydrogel has excellent viscosity. Chinese patent application CN112279961B discloses a method for preparing a light-responsive adhesive with strong adhesion under water and the obtained light-responsive adhesive, and the hydrogen bonding between nucleic acid bases is introduced by a one-pot method, and the obtained adhesive has excellent adhesion properties. However, the hydrogel obtained in the above-mentioned patent application CN106040113A swells but does not dissolve in water, and thus cannot be uniformly mixed with solid particles such as active substances and conductive agents to form slurry, so it cannot be used for lithium electric binders, and the binder prepared by Chinese patent application CN112279961B is hydrophobic because it does not contain polar monomers, so it is easy to swell or even dissolve in lithium ion battery electrolytes (oily solvents) to lose adhesion properties, and it cannot be used for lithium electric binders. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a lithium ion battery negative electrode bionic binder and a preparation method thereof, a lithium ion battery negative electrode slurry and a negative electrode, and introduces nucleic acid bases into a PAA-based lithium battery binder system. The lithium ion battery negative electrode bionic binder provided by the present invention can still maintain high adhesion in the electrolyte, and the electrode pole piece prepared by using the binder can still maintain the integrity of the electrode structure under high surface loading without powder falling off, and the formed battery has excellent cycle performance.
[0006] The present invention is specifically implemented through the following scheme.
[0007] The present invention provides a method for preparing a lithium ion battery negative electrode bionic binder, comprising the following steps:
[0008] The nucleic acid base is double-bond modified to obtain nucleic acid base acrylate; the nucleic acid base is one of adenine (A), thymine (T), guanine (G), cytosine (C) and uracil (U).
[0009] The bionic binder for negative electrode of lithium ion battery is prepared by using nucleic acid base acrylate and acrylic acid as monomers, water as solvent and initiator to initiate polymerization reaction under the protection of inert gas.
[0010] In a preferred embodiment of the present invention, nucleic acid base acrylate and acrylic acid monomer are dissolved in water to form a mixed solution, an initiator is added, vacuum is evacuated and a protective gas is introduced, and the temperature is raised to cause a polymerization reaction to prepare a bionic binder for the negative electrode of a lithium-ion battery.
[0011] In a preferred embodiment of the present invention, in the mixed solution, the total concentration of monomers is 10 wt.% to 25 wt.%.
[0012] In a preferred embodiment of the present invention, the nucleic acid base acrylate monomer accounts for 10% to 30% of the total molar amount of the monomers.
[0013] In a preferred embodiment of the present invention, the polymerization reaction temperature is 60° C. to 80° C., and the polymerization reaction time is 3 to 10 hours.
[0014] In a preferred embodiment of the present invention, the initiator includes one or more of ammonium persulfate (APS), potassium persulfate (KPS), and azobisisobutylamidine hydrochloride (AIBA), and the added amount of the initiator is 0.1wt.% to 0.5wt.% of the total weight of the monomers.
[0015] The invention provides a lithium ion battery negative electrode bionic binder prepared by the preparation method.
[0016] The present invention provides a negative electrode slurry for a lithium ion battery. The negative electrode slurry for the lithium ion battery is prepared by dispersing an active material, a conductive additive and the binder in water. In the mixture consisting of the active material, the conductive additive and the binder, the mass percentage of the active material is 92% to 95%, the mass percentage of the conductive additive is 1% to 2%, and the remainder is the binder, which is 100% in total.
[0017] The invention provides a lithium ion battery negative electrode, comprising a current collector and a lithium ion battery negative electrode material attached to the current collector; the lithium ion battery negative electrode material is obtained by coating the lithium ion battery negative electrode slurry on the current collector and drying it.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention provides a method for preparing a bionic binder for a lithium ion battery negative electrode with strong adhesion in an electrolyte, wherein nucleic acid bases are introduced into a PAA-based lithium electric binder system and applied to the negative electrode of a lithium ion battery. Specifically, the bionic binder is obtained by free radical copolymerization of nucleic acid base acrylate monomers and acrylic acid monomers, wherein nucleic acid bases are important molecules constituting life as basic units of DNA and RNA, and the ability of DNA and RNA to store and encode information originates from complementary base pairing interactions in a body fluid environment, i.e., the pairing of AT, GC and AU, so the binder containing nucleic acid bases in the present invention can also produce effective molecular recognition with the corresponding chemical components on a solid surface, thereby leading to adhesion behavior. The presence of the PAA chain gives the binder strong mechanical properties and intermolecular forces, ensuring the stability of the electrode structure during the battery cycle, and the strongly polar PAA molecular chain also ensures that the binder does not swell significantly in the electrolyte environment, so that the adhesion and mechanical strength of the binder do not decrease significantly. The binder still maintains high adhesion in the electrolyte, ensuring the stability of the electrode structure, no powder falling at a high surface load, and stable battery charge and discharge cycles.
[0020] The preparation method provided by the invention is green, environmentally friendly, simple and easy to implement; the obtained adhesive has good stability and strong adhesion, and is suitable for large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a physical picture of the lithium-ion battery electrode sheet after folding using the binder of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0023] The present invention is particularly directed to binders used in negative electrodes of lithium-ion batteries. Such binders are generally required to have the following properties:
[0024] (1) Good solubility, fast dissolution rate and high solubility.
[0025] (2) It does not swell in the electrolyte or has a small swelling coefficient and does not react with the electrolyte, thus ensuring stable performance.
[0026] (3) Good bonding performance, high mechanical strength and good flexibility.
[0027] (4) The electrochemical properties are stable and no redox reaction occurs within the operating voltage.
[0028] PAA is currently mainly used in silicon-based negative electrodes, which has high adhesion, but the cohesive force between PAA molecules is large, which leads to easy powder loss of the pole piece at high surface loading, affecting the battery cycle performance. In order to further improve its bonding performance, the present invention introduces nucleic acid bases into the PAA-based lithium battery binder system and applies it to the negative electrode of the lithium ion battery, wherein the nucleic acid bases in the binder molecular chain can ensure that the binder still has strong adhesion in the electrolyte liquid environment, and the presence of the PAA chain gives the binder strong mechanical properties and intermolecular forces, ensuring the stability of the electrode structure during the battery cycle, and the strong polarity of the PAA molecular chain also ensures that the binder does not swell significantly in the electrolyte environment, so that the adhesion and mechanical strength of the binder are not significantly reduced.
[0029] The components in the negative electrode of the lithium ion battery using the bionic binder of the present invention have strong binding force. The bionic binder of the present invention can maintain the integrity of the electrode structure at a high surface load without cracking due to its excellent adhesion ability, thereby significantly improving the cycle stability of the lithium ion battery.
[0030] Specifically, in response to the above requirements, the present invention provides a bionic binder for a negative electrode of a lithium-ion battery, wherein the binder is formed by free radical polymerization of nucleic acid base acrylate monomers and acrylic acid monomers in an aqueous solution.
[0031] The nucleic acid base acrylate monomer is prepared by double-bond modification of a nucleic acid base, and the nucleic acid base includes one of adenine (A), thymine (T), guanine (G), cytosine (C) and uracil (U).
[0032] In the present invention, the presence of nucleic acid bases can ensure that the binder still has strong adhesion in the electrolyte, and the formed slurry is not prone to powdering after drying, thereby ensuring the stability of the electrode structure when the active material expands. The presence of acrylic acid molecular chains enables the binder to have strong mechanical properties and intermolecular forces, and has no significant swelling in the electrolyte environment and a stable structure.
[0033] The lithium ion battery negative electrode bionic binder with strong adhesion in the electrolyte provided by the present invention can make the lithium battery negative electrode still maintain good stability under high load, and when the Si / C negative electrode using the binder is assembled into a battery, it shows excellent electrochemical performance. The present invention limits the nucleic acid base acrylate monomer to 10% to 30% of the total molar amount of the monomer. Within the above range, the comprehensive performance of the binder can be improved.
[0034] The present invention provides a method for preparing a lithium ion battery negative electrode bionic binder having strong adhesion in an electrolyte according to the above technical solution, comprising the following steps:
[0035] The nucleic acid base is double-bonded and modified to obtain nucleic acid base acrylate.
[0036] The bionic binder for negative electrode of lithium ion battery is prepared by using nucleic acid base acrylate and acrylic acid as monomers, water as solvent and initiator to initiate polymerization reaction under the protection of inert gas.
[0037] In the present invention, the polymerization reaction includes the following steps: mixing nucleic acid base acrylate monomer and acrylic acid monomer in an aqueous solution to form a mixed solution, adding an initiator, evacuating and introducing a protective gas, heating to carry out a polymerization reaction, and obtaining a lithium ion battery negative electrode bionic binder with strong adhesion in an electrolyte.
[0038] In the present invention, the following steps are used to modify the double bonds of nucleic acid bases:
[0039] (1) Dissolve 0.01 mol of nucleic acid base and 0.013 mol of triethylamine in 20 mL of dimethylformamide (DMF) and stir for 30 min in an ice bath;
[0040] (2) adding 0.011 mol of acryloyl chloride to the above reaction system under inert gas protection and reacting at room temperature for 6 hours;
[0041] (3) The above reactants are added into 200 mL of ether to precipitate to obtain the product, i.e., nucleic acid base acrylate monomer.
[0042] In the present invention, the nucleic acid base includes one of adenine (A), thymine (T), guanine (G), cytosine (C) and uracil (U).
[0043] In the present invention, the nucleic acid base acrylate monomer accounts for 10% to 30% of the total molar weight of the monomers, and more preferably 10%; in the mixed solution, the total monomer concentration is preferably 10 to 25 wt.%, and more preferably 20 wt.%; the concentration of the initiator is preferably 0.1 wt.% to 0.5 wt.%, and more preferably 0.2 wt.% of the total weight of the monomers.
[0044] In the present invention, the initiator includes one or more of ammonium persulfate (APS), potassium persulfate (KPS), and azobisisobutylamidine hydrochloride (AIBA). In the present invention, the water is preferably deionized water.
[0045] In the present invention, the polymerization reaction temperature is preferably 60-80°C, more preferably 70°C; the polymerization reaction time is preferably 3-10h, more preferably 5h. In the present invention, the polymerization reaction is preferably carried out in an inert gas atmosphere, more preferably a nitrogen atmosphere.
[0046] The present invention provides an application of a lithium ion battery negative electrode bionic binder in a lithium ion battery negative electrode material, preferably applied to a graphite negative electrode material. The lithium ion battery negative electrode bionic binder with strong adhesion in an electrolyte provided by the present invention enables the graphite negative electrode material to maintain good stability and adhesion under high load, and when a button cell is assembled using the graphite negative electrode of the lithium ion battery negative electrode bionic binder with strong adhesion in an electrolyte, excellent electrochemical performance is exhibited.
[0047] The invention provides a lithium ion battery negative electrode slurry, which is prepared by dispersing active materials, conductive additives and a binder in water; the binder is the lithium ion battery negative electrode bionic binder provided by the invention.
[0048] In the present invention, the active material preferably includes one or more of silicon material, silicon-carbon material, silicon-oxygen material and graphite; the conductive additive preferably includes one or more of SuperP, acetylene black and Ketjen black.
[0049] In the present invention, the method for preparing the negative electrode slurry of the lithium ion battery preferably comprises: mixing the active material, the conductive additive and the binder, and dispersing them in water by stirring to obtain the negative electrode slurry of the lithium ion battery. In the mixture consisting of the active material, the conductive additive and the binder, the mass percentage of the active material is 92% to 95%, the mass percentage of the conductive additive is 1% to 2%, and the remainder is the binder, which is 100% in total.
[0050] In the present invention, the water is preferably deionized water. In the present invention, the solid content of the lithium ion battery negative electrode slurry is preferably 30wt.% to 55wt.%, more preferably 45wt.%.
[0051] The present invention provides a lithium-ion battery negative electrode, comprising a current collector and a lithium-ion battery negative electrode material attached to the current collector; the lithium-ion battery negative electrode material is obtained by coating the lithium-ion battery negative electrode slurry described in the above technical solution on the current collector and drying it. In the present invention, the coating thickness of the lithium-ion battery negative electrode slurry on the current collector is preferably 200 to 400 microns. In the present invention, the current collector preferably comprises copper foil. In the present invention, the thickness of the current collector is preferably 8 microns. In the present invention, the coating is preferably carried out using an automatic coating machine. In the present invention, the drying is preferably vacuum drying.
[0052] In the present invention, the negative electrode of the lithium-ion battery is preferably a negative electrode sheet with a diameter of 12 mm.
[0053] The present invention also provides a lithium-ion battery, comprising the lithium-ion battery negative electrode described in the above technical solution. In the present invention, the preparation method of the lithium-ion battery preferably includes the following steps: placing the lithium-ion battery negative electrode in a glove box filled with argon gas to assemble into a 2032 button half-cell; using a pure lithium sheet as a counter electrode and Celgard 2300 as a diaphragm; the electrolyte uses a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC and DEC is 1:1) containing 1 mol / L lithium hexafluorophosphate (LiPF6), and adding 5% volume fraction of fluoroethylene carbonate (FEC) to obtain a lithium-ion battery.
[0054] The lithium ion battery negative electrode bionic binder with strong adhesion in the electrolyte provided by the present invention has excellent adhesion, can avoid cracking and powder loss of electrode pole pieces, and can relieve the internal stress generated by the expansion of active materials, effectively inhibit the collapse of the electrode structure caused by the fragmentation of active materials, maintain the integrity of the electrode structure, and improve the electrochemical stability of the lithium ion battery.
[0055] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] Example 1
[0057] A method for preparing a lithium ion battery negative electrode bionic binder comprises the following steps:
[0058] (1) Dissolve 0.01 mol of adenine and 0.013 mol of triethylamine in 20 mL of dimethylformamide (DMF) and stir for 30 min in an ice bath.
[0059] (2) 0.011 mol of acryloyl chloride was added to the above reaction system under inert gas protection and reacted at room temperature for 6 hours.
[0060] (3) The above reactants were added into 200 mL of ether to precipitate to obtain the product, i.e., adenine acrylate monomer.
[0061] (4) 0.01 mol of adenine acrylate monomer, 0.09 mol of acrylic acid monomer and water were mixed and stirred to form a mixed solution with a concentration of 20 wt.%.
[0062] (5) Add 0.01 g of KPS initiator, evacuate the reaction flask and circulate nitrogen three times to remove oxygen from the flask.
[0063] (6) The temperature is raised to 75° C. to cause a polymerization reaction, and the reaction is continued for 4 hours to obtain a bionic binder for the negative electrode of a lithium-ion battery.
[0064] Example 2
[0065] A method for preparing a lithium ion battery negative electrode bionic binder comprises the following steps:
[0066] (1) Dissolve 0.01 mol thymine and 0.013 mol triethylamine in 20 mL dimethylformamide (DMF) and stir for 30 min in an ice bath.
[0067] (2) 0.011 mol of acryloyl chloride was added to the above reaction system under inert gas protection and reacted at room temperature for 6 hours.
[0068] (3) The above reactants were added into 200 mL of ether to precipitate to obtain the product, i.e., adenine acrylate monomer.
[0069] (4) 0.01 mol of thymine acrylate monomer, 0.09 mol of acrylic acid monomer and water were mixed and stirred to form a mixed solution with a concentration of 20 wt.%.
[0070] (5) Add 0.01 g of KPS initiator, evacuate the reaction flask and circulate nitrogen three times to remove oxygen from the flask.
[0071] (6) The temperature is raised to 75° C. to cause a polymerization reaction, and the reaction is continued for 4 hours to obtain a bionic binder for the negative electrode of a lithium-ion battery.
[0072] Example 3
[0073] A method for preparing a lithium ion battery negative electrode bionic binder comprises the following steps:
[0074] (1) Dissolve 0.01 mol guanine and 0.013 mol triethylamine in 20 mL dimethylformamide (DMF) and stir for 30 min in an ice bath.
[0075] (2) 0.011 mol of acryloyl chloride was added to the above reaction system under inert gas protection and reacted at room temperature for 6 hours.
[0076] (3) The above reactants were added into 200 mL of ether to precipitate to obtain the product, i.e., adenine acrylate monomer.
[0077] (4) 0.01 mol of guanine acrylate monomer, 0.09 mol of acrylic acid monomer and water were mixed and stirred to form a mixed solution with a concentration of 20 wt.%.
[0078] (5) Add 0.01 g of KPS initiator, evacuate the reaction flask and circulate nitrogen three times to remove oxygen from the flask.
[0079] (6) The temperature is raised to 75° C. to cause a polymerization reaction, and the reaction is continued for 4 hours to obtain a bionic binder for the negative electrode of a lithium-ion battery.
[0080] Example 4
[0081] A method for preparing a lithium ion battery negative electrode bionic binder comprises the following steps:
[0082] (1) Dissolve 0.01 mol cytosine and 0.013 mol triethylamine in 20 mL dimethylformamide (DMF) and stir for 30 min in an ice bath.
[0083] (2) 0.011 mol of acryloyl chloride was added to the above reaction system under inert gas protection and reacted at room temperature for 6 hours.
[0084] (3) The above reactants were added into 200 mL of ether to precipitate to obtain the product, i.e., adenine acrylate monomer.
[0085] (4) 0.01 mol of cytosine acrylate monomer, 0.09 mol of acrylic acid monomer and water were mixed and stirred to form a mixed solution with a concentration of 20 wt.%.
[0086] (5) Add 0.01 g of KPS initiator, evacuate the reaction flask and circulate nitrogen three times to remove oxygen from the flask.
[0087] (6) The temperature is raised to 75° C. to cause a polymerization reaction, and the reaction is continued for 4 hours to obtain a bionic binder for the negative electrode of a lithium-ion battery.
[0088] Example 5
[0089] A method for preparing a lithium ion battery negative electrode bionic binder comprises the following steps:
[0090] (1) Dissolve 0.01 mol uracil and 0.013 mol triethylamine in 20 mL dimethylformamide (DMF) and stir for 30 min in an ice bath.
[0091] (2) 0.011 mol of acryloyl chloride was added to the above reaction system under inert gas protection and reacted at room temperature for 6 hours.
[0092] (3) The above reactants were added into 200 mL of ether to precipitate to obtain the product, i.e., adenine acrylate monomer.
[0093] (4) 0.01 mol of uracil acrylate monomer, 0.09 mol of acrylic acid monomer and water were mixed and stirred to form a mixed solution with a concentration of 20 wt.%.
[0094] (5) Add 0.01 g of KPS initiator, evacuate the reaction flask and circulate nitrogen three times to remove oxygen from the flask.
[0095] (6) The temperature is raised to 75° C. to cause a polymerization reaction, and the reaction is continued for 4 hours to obtain a bionic binder for the negative electrode of a lithium-ion battery.
[0096] Example 6
[0097] A method for preparing a lithium ion battery negative electrode bionic binder comprises the following steps:
[0098] (1) Dissolve 0.01 mol uracil and 0.013 mol triethylamine in 20 mL dimethylformamide (DMF) and stir for 30 min in an ice bath.
[0099] (2) 0.011 mol of acryloyl chloride was added to the above reaction system under inert gas protection and reacted at room temperature for 6 hours.
[0100] (3) The above reactants were added into 200 mL of ether to precipitate to obtain the product, i.e., adenine acrylate monomer.
[0101] (4) 0.03 mol of uracil acrylate monomer, 0.07 mol of acrylic acid monomer and water were mixed and stirred to form a mixed solution with a concentration of 20 wt.%.
[0102] (5) Add 0.01 g of KPS initiator, evacuate the reaction flask and circulate nitrogen three times to remove oxygen from the flask.
[0103] (6) The temperature is raised to 75° C. to cause a polymerization reaction, and the reaction is continued for 4 hours to obtain a bionic binder for the negative electrode of a lithium-ion battery.
[0104] Example 7
[0105] A method for preparing a lithium ion battery negative electrode bionic binder comprises the following steps:
[0106] (1) Dissolve 0.01 mol uracil and 0.013 mol triethylamine in 20 mL dimethylformamide (DMF) and stir for 30 min in an ice bath.
[0107] (2) 0.011 mol of acryloyl chloride was added to the above reaction system under inert gas protection and reacted at room temperature for 6 hours.
[0108] (3) The above reactants were added into 200 mL of ether to precipitate to obtain the product, i.e., adenine acrylate monomer.
[0109] (4) 0.02 mol of uracil acrylate monomer, 0.08 mol of acrylic acid monomer and water were mixed and stirred to form a mixed solution with a concentration of 20 wt.%.
[0110] (5) Add 0.01 g of KPS initiator, evacuate the reaction flask and circulate nitrogen three times to remove oxygen from the flask.
[0111] (6) The temperature is raised to 75° C. to cause a polymerization reaction, and the reaction is continued for 4 hours to obtain a bionic binder for the negative electrode of a lithium-ion battery.
[0112] Example 8
[0113] A method for preparing a lithium ion battery negative electrode bionic binder comprises the following steps:
[0114] (1) Dissolve 0.01 mol uracil and 0.013 mol triethylamine in 20 mL dimethylformamide (DMF) and stir for 30 min in an ice bath.
[0115] (2) 0.011 mol of acryloyl chloride was added to the above reaction system under inert gas protection and reacted at room temperature for 6 hours.
[0116] (3) The above reactants were added into 200 mL of ether to precipitate to obtain the product, i.e., adenine acrylate monomer.
[0117] (4) 0.01 mol of uracil acrylate monomer, 0.09 mol of acrylic acid monomer and water were mixed and stirred to form a mixed solution with a concentration of 20 wt.%.
[0118] (5) Add 0.01 g of KPS initiator, evacuate the reaction flask and circulate nitrogen three times to remove oxygen from the flask.
[0119] (6) The temperature is raised to 70° C. to cause a polymerization reaction, and the reaction is continued for 4 hours to obtain a bionic binder for the negative electrode of a lithium-ion battery.
[0120] Example 9
[0121] A method for preparing a lithium ion battery negative electrode bionic binder comprises the following steps:
[0122] (1) Dissolve 0.01 mol uracil and 0.013 mol triethylamine in 20 mL dimethylformamide (DMF) and stir for 30 min in an ice bath.
[0123] (2) 0.011 mol of acryloyl chloride was added to the above reaction system under inert gas protection and reacted at room temperature for 6 hours.
[0124] (3) The above reactants were added into 200 mL of ether to precipitate to obtain the product, i.e., adenine acrylate monomer.
[0125] (4) 0.01 mol of uracil acrylate monomer, 0.09 mol of acrylic acid monomer and water were mixed and stirred to form a mixed solution with a concentration of 25 wt.%.
[0126] (5) Add 0.01 g of KPS initiator, evacuate the reaction flask and circulate nitrogen three times to remove oxygen from the flask.
[0127] (6) The temperature is raised to 75° C. to cause a polymerization reaction, and the reaction is continued for 4 hours to obtain a bionic binder for the negative electrode of a lithium-ion battery.
[0128] Example 10
[0129] A method for preparing a lithium ion battery negative electrode bionic binder comprises the following steps:
[0130] (1) Dissolve 0.01 mol uracil and 0.013 mol triethylamine in 20 mL dimethylformamide (DMF) and stir for 30 min in an ice bath.
[0131] (2) 0.011 mol of acryloyl chloride was added to the above reaction system under inert gas protection and reacted at room temperature for 6 hours.
[0132] (3) The above reactants were added into 200 mL of ether to precipitate to obtain the product, i.e., adenine acrylate monomer.
[0133] (4) 0.01 mol of uracil acrylate monomer, 0.09 mol of acrylic acid monomer and water are mixed and stirred to form a mixed solution with a concentration of 10 wt.%.
[0134] (5) Add 0.01 g of KPS initiator, evacuate the reaction flask and circulate nitrogen three times to remove oxygen from the flask.
[0135] (6) The temperature is raised to 75° C. to cause a polymerization reaction, and the reaction is continued for 4 hours to obtain a bionic binder for the negative electrode of a lithium-ion battery.
[0136] Comparative Example 1
[0137] Comparative Example 1 is a mixture of styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) in a mass ratio of 3:2.
[0138] The performance tests were performed on the adhesives prepared in the above examples and comparative examples:
[0139] Electrochemical performance test:
[0140] (1) A negative electrode active material graphite, a conductive additive (Super P) and a binder are mixed in a mass ratio of 95:2:3, and are uniformly dispersed in deionized water by stirring to obtain a uniformly mixed lithium ion battery negative electrode slurry with a solid content of 45 wt.%.
[0141] (2) The lithium-ion battery negative electrode slurry in (1) is uniformly coated on a copper foil 8 μm thick using an automatic coating machine to a coating thickness of 300 μm, and then placed in a vacuum drying oven to dry and remove the solvent; after drying, it is cut into negative electrode sheets with a diameter of 12 mm.
[0142] (3) The negative electrode sheet prepared in (2) was transferred to a glove box filled with argon and assembled into a 2032 button half-cell; a pure lithium sheet was used as the counter electrode and Celgard 2300 was used as the separator; the electrolyte was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC and DEC was 1:1) containing 1 mol / L lithium hexafluorophosphate (LiPF6), and 5% by volume of fluoroethylene carbonate (FEC) was added.
[0143] (4) The button cell assembled in (3) was left to stand for 24 h, and then cycled once at a rate of 0.1 C within a voltage range of 0.01 to 2.00 V, and then charged and discharged at a rate of 0.5 C.
[0144] Adhesion test:
[0145] The electrode plates were subjected to a peeling test using an MTS mechanical testing machine (E43.104) to evaluate the bonding strength of the adhesive. The plates prepared using the above method were immersed in the above electrolyte and kept at 40°C for 72 hours. The adhesion strength of the electrodes was then tested using a 180° peeling test. The specific operation was to take the plate to be tested, cut a sample of 100 mm in length and 20 mm in width with a blade, attach one side of the sample loaded with active material to a 3M transparent tape (20 mm), pull the tape at an angle of 180° and a constant displacement rate of 2 mm / s, and measure the peeling force.
[0146] The peeling force of the lithium-ion battery negative electrode bionic binder was tested by the test example method to characterize its adhesion. The results are shown in Table 1. The above-mentioned pole piece was rolled and folded to observe its powder loss phenomenon to further characterize its adhesion. The results are shown in Table 2.
[0147] The method of the test example was used to apply the lithium ion battery negative electrode bionic binder to the negative electrode and assemble a 2032 button half-cell to test the electrochemical performance. The results are shown in Table 3.
[0148] Table 1 Adhesion test data of Examples 1 to 10 and Comparative Example 1
[0149] serial number Adhesion force F(N) Example 1 6.78 Example 2 5.12 Example 3 5.88 Example 4 5.76 Example 5 6.25 Example 6 6.32 Example 7 6.29 Example 8 6.24 Example 9 6.2 Example 10 6.17 Comparative Example 1 1.03
[0150] It can be seen from Table 1 that, compared with the SBR / CMC binder, the lithium ion battery negative electrode bionic binder prepared by the present invention has stronger adhesion in the electrolyte.
[0151] Table 2 Description of the winding state of the pole pieces of Examples 1 to 10 and Comparative Example 1
[0152]
[0153]
[0154] It can be seen from Table 2 that, compared with the SBR / CMC binder, the lithium ion battery negative electrode bionic binder prepared by the present invention has stronger adhesion under high loading.
[0155] Figure 1 The following are the actual pictures of the lithium ion battery electrode sheets after folding using the binders of Example 1 and Comparative Example 1. It can be seen that the Comparative Example 1 has serious creases, and there are problems of powder loss and cracking. The Example 1 does not have the problem of powder loss.
[0156] Table 3 Electrochemical cycle performance data of Examples 1 to 10 and Comparative Example 1
[0157]
[0158] From the results in Table 3, it can be seen that the surface loading of the lithium ion battery negative electrode bionic binder provided by the present invention is 12 mg / cm 2 When the thick electrode is used, the first-week coulomb efficiency is above 88%, and the capacity retention rate after 500 cycles is above 93%. However, the binder SBR / CMC in comparative example 1 has a first-week coulomb efficiency of 87.1%, and a capacity retention rate of only 90% after 500 cycles. It can be seen that the bionic binder for the negative electrode of the lithium ion battery of the present invention can still maintain the cycle stability of the graphite negative electrode material under high surface loading.
[0159] The lithium ion battery negative electrode bionic binder provided by the present invention can ensure the structural stability of the electrode during the cycle process through excellent adhesion ability, and significantly improve the cycle stability of the lithium ion battery. The lithium ion battery negative electrode bionic binder provided by the present invention is water-soluble, green and environmentally friendly, and its structure is easy to control, which can well meet the negative electrode preparation and production requirements.
[0160] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. A method for preparing a bionic binder for a negative electrode of a lithium ion battery, characterized in that: The following steps are involved: Double bond modification of nucleic acid bases is performed to obtain nucleic acid base acrylate; the nucleic acid base is one of adenine, thymine, guanine, cytosine and uracil; The bionic binder for negative electrode of lithium ion battery is prepared by using nucleic acid base acrylate and acrylic acid as monomers, water as solvent and initiator to initiate polymerization reaction under the protection of inert gas.
2. The method for preparing the negative electrode bionic binder for lithium ion batteries according to claim 1, characterized in that: The nucleic acid base acrylate monomer and acrylic acid monomer are dissolved in water to form a mixed solution, an initiator is added, vacuum is evacuated, a protective gas is introduced, and the temperature is increased to cause a polymerization reaction to prepare a lithium ion battery negative electrode bionic binder.
3. The method for preparing the negative electrode bionic binder for lithium ion batteries according to claim 1, characterized in that: The nucleic acid base acrylate monomer accounts for 10% to 30% of the total molar amount of the monomers.
4. The method for preparing the negative electrode bionic binder for lithium ion batteries according to claim 2, characterized in that: In the mixed solution, the total concentration of monomers is 10 wt.% to 25 wt.%.
5. The method for preparing the negative electrode bionic binder for lithium ion batteries according to claim 1, characterized in that: The polymerization reaction temperature is 60° C. to 80° C., and the polymerization reaction time is 3 h to 10 h.
6. The method for preparing the bionic binder for negative electrode of lithium ion battery according to claim 1, characterized in that: The initiator is one or more of ammonium persulfate, potassium persulfate, and azobisisobutylamidine hydrochloride.
7. The method for preparing the bionic binder for negative electrode of lithium ion battery according to claim 1, characterized in that: The added amount of the initiator is 0.1 wt.% to 0.5 wt.% of the total weight of the monomers.
8. A bionic binder for negative electrode of a lithium ion battery prepared according to the preparation method according to any one of claims 1 to 7.
9. A negative electrode slurry for a lithium ion battery, characterized in that: The negative electrode slurry of the lithium-ion battery is prepared by dispersing active materials, conductive additives and the binder described in claim 8 in water. In the mixture consisting of the active materials, conductive additives and binder, the mass percentage of the active materials is 92% to 95%, the mass percentage of the conductive additive is 1% to 2%, and the remainder is the binder, which is 100% in total.
10. A negative electrode for a lithium-ion battery, comprising a current collector and a negative electrode material for a lithium-ion battery attached to the current collector; the negative electrode material for a lithium-ion battery is obtained by coating the negative electrode slurry for a lithium-ion battery according to claim 9 on the current collector and drying the coating.
